Groundwater mapping model by using Modified Drastic Model and AHP / Nur Akma Zainul Abidin - Zainul Abidin, Nur Akma (2018)
Various application has been used to identify the groundwater suitability area. This thesis entitled ” Groundwater Mapping Model Using Modified DRASTIC Model and AHP”. The aim of this project is to create modelling of the groundwater area for Perlis state. The objectives are to prepare thematic maps of seven parameters, to apply modified DRASTIC model and Analytical Hierarchy Process (AHP) techniques for groundwater selection and lastly to create modelling of groundwater potential area for Perlis state. The seven parameters are land use map, rainfall, geology, drainage density, lineament density, elevation and slope. The maps are processed and produced using ArcGIS software. It then overlayed using weighted overlay analysis. The result is presented in 2D map and 3D model. The 3D model is produced using ArcScene 10.4.1. It is shown that rainfall has the highest influence compared to other factors. The result shows that the highest potential area is in the north of Perlis. The groundwater application is important to gain more water sources so that we can preserve this natural sources for future generation.